The Effect Of Industrial Agglomeration, Education Level, Population And Labor On Regional Income Inequality In Sumatera Island (Panel Data Analysis 2015 – 2024) From The Perspective Of Islamic Economics - Elvia Laili Putri; Ghina Ulfah Saefurrohman; Dimas Pratomo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study analyzes the influence of industrial agglomeration, education level, population, and workforce on regional income inequality in Sumatra Island for the period 2015–2024 from an Islamic economic perspective. Data were analyzed using the panel data method and measured by the Gini coefficient. The results of the study indicate that income inequality between provinces in Sumatra is fluctuating but generally still low. Industrial agglomeration, education level, population, and workforce have been shown to influence income inequality. The principle of Islamic economic justice emphasizes the importance of equitable distribution of wealth so that community welfare can be achieved. These findings recommend the need for policies for equitable development and improving the quality of human resources to reduce income inequality in Sumatra Island.